2017
DOI: 10.1002/pen.24514
|View full text |Cite
|
Sign up to set email alerts
|

Structuring and characterization of a novel microporous PVDF membrane with semi‐interpenetrating polymer networks for vacuum membrane distillation

Abstract: In this paper, by using the non-solvent induced phase separation (NIPS) process, a new microporous membrane with semi-interpenetrating polymer network (semi-IPN) was produced in which PDMS polymer is crosslinked and PVDF polymer is linear. For the fabrication of the membrane, tetraethylorthosilicate (TEOS) was used as the crosslinking agent and dibutyltin dilaurate (DBTDL) was used as the catalyst. By changing the mass ratio of PDMS/TEOS, the structure and the performance of the prepared membrane were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…No scientific work of this compound has been reported in gas separation. However PVDF was extensively investigated as membrane in other areas of membrane processes . Considering some published papers on GO containing MMMs, it can be concluded that GO with high aspect ratio is an inspiring filler for efficient MMM construction in practical gas separation application.…”
Section: Introductionmentioning
confidence: 99%
“…No scientific work of this compound has been reported in gas separation. However PVDF was extensively investigated as membrane in other areas of membrane processes . Considering some published papers on GO containing MMMs, it can be concluded that GO with high aspect ratio is an inspiring filler for efficient MMM construction in practical gas separation application.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, except from being widely used in conventional filtration processes (micro and ultrafiltration), PVDF membranes are lately regarded as potential candidates for membrane contactor, membrane reactor and membrane distillation processes . Most of the asymmetric PVDF membranes are produced by the immersion‐precipitation (IP) method due to the simplicity of the process and the ease of PVDF dissolution in a range of organic solvents, while nonsolvent‐induced phase separation processes are also applied . The major attempts to fine tune the morphology and pore structure of asymmetric PVDF membranes and make them appropriate for DCMD processes, had initially focused on the preparation conditions including the choice of solvent, the evaporation period between casting and coagulation, the air gap distance , the effect of coagulation bath medium and temperature (i.e., sequence of liquid–liquid demixing and crystallization, and/or dominance of crystallization or liquid–liquid demixing), the postcasting heat treatment , and the effect of low and high MW nonsolvent additives that are usually hydrophilic ones and can function as pore formers.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption peaks at 612 and 762 cm –1 were ascribed to the −CF 2 – group (this could be attributed to PVDF and perfluorooctanoic acid, Figure e). The adsorption peak at 1070 cm –1 was ascribed to −CF 2 – and −CH 2 – groups . The adsorption peaks at 1207 and 1402 cm –1 were attributed to the −CH 2 – group of PVDF.…”
Section: Resultsmentioning
confidence: 94%